Is The Economy Really Growing? An Empirical Study in European Union Countries - Moh Aldo Fahrul Azmi; Mahameru Rosy Rochmatullah (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to examine the effects of inflation, Foreign Direct Investment (FDI), public debt, and poverty on economic growth in European Union countries currently experiencing recession. The research utilizes secondary data from sources such as the World Bank, Eurostat, European Parliament, International Monetary Fund (IMF), European Central Bank, Organization for Economic Cooperation and Development (OECD), and other relevant sources from the years 2018 to 2022. By employing classical assumption tests for cross-sectional regression, the results indicate that public debt significantly influences the level of economic growth, while inflation, foreign direct investment, and poverty variables do not significantly affect the economic growth rate. The implication is that governments should not only pursue high economic growth figures but also focus on ensuring that economic growth is of high quality and equitable, considering other aspects such as societal welfare and the satisfaction of the population.